Impact of neoadjuvant chemotherapy and postoperative adjuvant chemotherapy cycles on survival of patients with advanced-stage ovarian cancer. - Young Shin Chung; Yun-Ji Kim; Inha Lee; Jung-Yun Lee; Eun Ji Nam; Sunghoon Kim; Sang Wun Kim; Young Tae Kim (PLoS ONE)
Background There is currently no consensus regarding the optimal number of chemotherapy cycles to be administered before and after interval debulking surgery (IDS) in patients with advanced ovarian cancer. This study aimed to evaluate the impact of the number of neoadjuvant chemotherapy (NAC) and postoperative adjuvant chemotherapy (POAC) cycles on the survival of patients with advanced ovarian cancer undergoing NAC/IDS/POAC. Methods We retrospectively reviewed data from 203 patients who underwent NAC/IDS/POAC at Yonsei Cancer Hospital between 2006 and 2016. All patients underwent taxane plus carboplatin chemotherapy for NAC and POAC. The patient outcomes were analyzed according to the number of NAC, POAC, and total chemotherapy (NAC+POAC) cycles. Results Patients who received fewer than 6 cycles of total chemotherapy (n = 8) had poorer progression-free survival (PFS) and overall survival (OS) than those completing at least 6 cycles (p = 0.005 and p<0.001, respectively). Among patients who completed at least 6 cycles of total chemotherapy (n = 189), Kaplan-Meier analysis revealed no significant difference in either PFS or OS according to the number of NAC cycles (1-3 vs. ≥4; p = 0.136 and p = 0.267, respectively). Among patients who experienced complete remission after 3 cycles of POAC (n = 98), the addition of further POAC cycles did not improve the PFS or OS (3 vs. ≥4; p = 0.641 and p = 0.104, respectively). Conclusion IDS after 4 cycles of NAC may be a safe and effective option when completing 6 cycles of total chemotherapy. Furthermore, the addition of more than 3 cycles of POAC does not appear to influence the survival of patients achieving completion remission after 3 cycles of POAC.